Pengaruh Kebijakan Dividen, Keputusan Investasi, Pertumbuhan Perusahaan dan Profitabilitas terhadap Nilai Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia (2022) - Mariana Mariana; Martinus Budiantara (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of dividend policy, investment decisions, company growth, and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. The company value is measured using the Price to Book Value (PBV) ratio, while the independent variables include dividend policy measured by the Dividend Payout Ratio (DPR), investment decisions using the Price Earnings Ratio (PER), company growth measured by asset growth, and profitability measured by the Net Profit Margin (NPM). This research utilizes a quantitative approach with multiple linear regression techniques to analyze secondary data obtained from the companies' annual financial reports. The findings indicate that dividend policy, investment decisions, company growth, and profitability simultaneously have a significant impact on the company's value. Partially, dividend policy, investment decisions, and company growth have a significant positive effect on company value, while profitability shows a more varied influence. These findings highlight the importance of company management in considering consistent dividend policies, strategic investment decisions, and effective profitability management to enhance company value and attract investors.